Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 10 - Introduction to Differential Equations - 10.4 First-Order Linear Equations - Exercises - Page 524: 20



Work Step by Step

Given $$x y^{\prime}+y=e^{x}, \quad y(1)=3$$ Then $$ y^{\prime}+\frac{1}{x}y=\frac{1}{x}e^{x} $$ This a linear equation with $p(x) =\frac{1}{x}$ and $q(x) =\frac{1}{x}e^{x} $, so \begin{align*} \mu(x) &= e^{\int p(x)dx}\\ &=e^{\int\frac{1}{x} dx}\\ &= e^{\ln x}\\ &=x \end{align*} Hence the general solution is \begin{align*} \mu(x) y &=\int \mu (x)xq(x)dx\\ x y&=\int \frac{x}{x}e^{x}dx \\ &=\int e^{x}dx\\ &=e^{x}+C \end{align*} Then $$ y= \frac{1}{x}e^{x}+C \frac{1}{x}$$ Since $ y(1)= 3 $, then $C= 3-e$, and hence $$y=\frac{e^{x}}{x}+\frac{3-e}{x}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.